2015 2nd International Conference on Pattern Recognition and Image Analysis (IPRIA) 2015
DOI: 10.1109/pria.2015.7161637
|View full text |Cite
|
Sign up to set email alerts
|

Object tracking with occlusion handling using mean shift, Kalman filter and Edge Histogram

Abstract: This paper propose an algorithm that uses Mean Shift and Kalman Filter for object tracking. Also this method uses Edge Histogram for occlusion handling. Firstly, we use Mean Shift algorithm to obtain center of desired object. But the robust of tracking is not very well, so we use Kalman Filter to improve the effect of tracking. Bhattacharyya coefficient and Edge Histogram are used for finding out both partial and full occlusions. With this approach we can track the object more accurately. The results prove tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Volleyball is both physically and conceptually estimated by event units, because the true value of physical states is impossible to obtain. During an event cell, if the ball track has a continuous curve without sharp gaps and all projected 2D image coordinates are within the area of the ball in the image frame, we determine that the ball tracking of the event cell is successful [25]. To visualize the tracking results, we selected a test sequence and plotted the tracked 3D track in the figure, figure 10.…”
Section: ) Color/grayscale Figuresmentioning
confidence: 99%
“…Volleyball is both physically and conceptually estimated by event units, because the true value of physical states is impossible to obtain. During an event cell, if the ball track has a continuous curve without sharp gaps and all projected 2D image coordinates are within the area of the ball in the image frame, we determine that the ball tracking of the event cell is successful [25]. To visualize the tracking results, we selected a test sequence and plotted the tracked 3D track in the figure, figure 10.…”
Section: ) Color/grayscale Figuresmentioning
confidence: 99%
“…Object tracking has various applications such as in security and surveillance systems which use visual data [14], self-driving cars [15], traffic management [16], improved medical therapy, customer behavior analysis [17], interactive game design, design of futuristic video effects, etc. Many algorithms like Mean-shift [18], Camshift [19] etc were developed for this purpose, but it is found that they do not show efficient real-time performance.…”
Section: Literature Surveymentioning
confidence: 99%
“…(7) According to Equation (7), the motion vectors of m p and m q in Cartesian coordinates are defined as (u p − v p ) and (u q − v q ), respectively, where l 𝜖S l and 𝜃𝜖S 𝜃 , and N (p) is the neighborhood of p. The energy function should be minimized to obtain a good performance. Meanwhile, the first term enforces choosing the higher confidence of the motion kernel for each pixel, and the second term encourages the smoothness of the nearby motion kernels.…”
Section: Blur Kernel Optimizationmentioning
confidence: 99%
“…Second, the smallest error of the initial value might cause drastic changes in the solution, which is referred to as butterfly effects [4,5]. Although Bayesian state estimation techniques such as particle [6] and Kalman filter [7] filters might solve these problems, the important thing is that a single measurement might not be enough for accurately estimating the location of the object. Accordingly, some deep learning-based methods may be integrated with some object trackers in order to reduce these problems.…”
Section: Introductionmentioning
confidence: 99%